Determinants of Inpatient Nurse Performance: The Mediating Role of Work Quality in A Type B Public Hospital - Eugenia Natalsha Putri Parorrongan; Alih Germas Kodyat; Dicky Yulius Pangkey (Jurnal Ners, 2026)
Nurse performance is essential for ensuring hospital service quality and patient safety. Although workload and work motivation influence performance, the mediating role of work quality remains insufficiently explored in regional public hospitals. The aim of this research is to analyze the effects of workload and work motivation on nurse performance, with work quality as a mediating variable, among inpatient nurses at RSUD Kendari City. A quantitative cross-sectional study was conducted among 103 inpatient nurses selected from 139 using the Slovin formula and proportional random sampling. Data were collected through validated questionnaires and analyzed using path analysis and the Sobel test. Based on the research results, it was found that workload had a significant negative effect on work quality (p<0.05) but no direct effect on nurse performance. Work motivation significantly improved work quality (p<0.001) but did not directly affect performance. Work quality significantly enhanced nurse performance and fully mediated the relationship between workload, work motivation, and performance. The model explained 77.5% of the variance in nurse performance (Adjusted R²=0.775). It can be concluded that improving work quality is fundamental to enhancing nurse performance. Hospital management should strengthen workload management, foster work motivation, and implement strategies that continuously improve work quality.